2017
DOI: 10.3233/jad-170634
|View full text |Cite
|
Sign up to set email alerts
|

Co-Localization of Glia Maturation Factor with NLRP3 Inflammasome and Autophagosome Markers in Human Alzheimer’s Disease Brain

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by the presence of intracellular neurofibrillary tangles (NFTs) containing hyper-phosphorylated tau, and the extracellular deposition of amyloid plaques (APs) with misfolded amyloid–β (Aβ) peptide. Glia maturation factor (GMF), a highly conserved pro-inflammatory protein, isolated and cloned in our laboratory has been shown to activate glial cells leading to neuroinflammation and neurodegeneration in AD. We hypothesized that infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 60 publications
6
84
0
Order By: Relevance
“…Neuroinflammation plays a crucial role during AD progression. We have previously shown that GMF plays a crucial role in the AD pathophysiology including neurodegeneration [17,23,24]. Therefore, we believe that GMF could potentially be an attractive therapeutic target against AD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neuroinflammation plays a crucial role during AD progression. We have previously shown that GMF plays a crucial role in the AD pathophysiology including neurodegeneration [17,23,24]. Therefore, we believe that GMF could potentially be an attractive therapeutic target against AD.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the microglial cells initiates a cascade of events that ultimately lead to neurodegeneration and AD pathophysiology. Proinflammatory mediator GMF has been shown to be expressed at elevated levels in AD patients [17,22-25,27]. We therefore believe that GMF represents a novel and an attractive therapeutic target to disrupt glia-neuron interactions and possibly delay and/or halt the progression of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3G, 3H), which we accordingly named the "inflammasome" and "anti-inflammasome" modules. The NLRP3 inflammasome is assembled downstream of cellular stressors and activated by the detection of various stimuli 13 , including pathological Abeta 49,50 , to promote pro-inflammatory states. Similarly, pathological Abeta rapidly and specifically stimulates the expression of the inflammasome module eigengene in microglia, both in vivo and in vitro ( Fig.…”
Section: Identification Of the Inflammasome And Anti-inflammasome Relmentioning
confidence: 99%